Expected protective role of Physalis pubescens L. plant extract against neuronal impairment associated with diabetes in rats - Heba Salah El-Din Fathy Hamed; Fawzy Ali Attaby (2022)
(3eQV GdScQj gh GVWQGH eRef jfJL Yfg GQJaGY GdScQ aj GdOe hfbU CfShdjf GdOe hjJSHH aj HYV GdGVWQGHGJ GdYUHjI(B. (3GdgOa ef GdOQGSI GdMGdjI gh Jbjje GdJCKjQ GdhbGFj GdeQJbH dYUjQ GdMQfcT VO GdVQQ GdYUHj aj PchQ GdLQPGf GdHjVGA GdeUGHI HOGA GdScQj GdeSJMK ef(B. STZ (3Je JbSje (B30(3LQP Edj (B5 (3eLehYGJ QFjSjg cd eLehYg JMJhj Ydj (B6 (3aFQGf, Ghd eLehYg gj GdeLehYI GdVGHWI Jdc GdeLehYI GdSdjeI GdJj de JJdaj Cj YdGL, GdeLehYI GdKGfjI Je EYWGDgG (B5 (3ed jhejG ef YUjQ GdMQfcT, GdeLehYI GdKGdKI gj GdJj Je MbfgG H` (B55 (3eLe (B/ (3cLe ef (BSTZ (3HOhf Cj YdGL, GdeLehYI GdQGHYI gj GdaFQGf GdeUGHI HGdScQj h Je YdGLgG HYUjQ GdMQfcT, GdeLehYI GdNGeSI LQPGf eUGHg HGdScQj hJe YdGLgG HGdejJGahQef (B500 (3eLe (B/ (3cLe h eOg GdYdGL GSJeQJ deOg (B28 (3jhe(B. (3aj fgGjI GdJLQHI Je bWY QCS SJg aFQGf ef cd eLehYI hJTQjM Ydi GdahQ ddMUhd Ydi bTQI GdOeGZ deRjO ef GdJLGQH GdHjhcjejGFjI hGdLRjFjI hGdfSjLjI(B. (3eLehYg GdaFQGf GdJj JdbJ (BSTZ (3abW cGfJ eSJhjGJ GdLdhchR h(BIL- 1gb (3h(BTNF-ga (3h(BNO (3h(BBax (3h(BMDA (3hGdMeV Gdfhhj GdQjHhRj GdeQSGd d (Bcaspase-3 (3GYdj HTcd edMhX Yf eLehYg GdVhGHW(B. (3Ydj GdfbjV cGfJ eSJhjGJ (Bmonoamine (3h(BGSH (3h(BBDNF (3h(BBcl-2 (3hGdMeV Gdfhhj GdQjHhRj GdeQSGd dcd ef (BSOD (3h(BGpx (3h(BGR (3h(BCAT (3Gbd HTcd cHjQ ef GdVhGHW(B. (3GjVG dhMX aj gPg GdeLehYI HYV GdJZjjQGJ aj GdJTQjM GdeQVj dCfSLI GdOeGZ(B. (3hdcf GdeLehYGJ GdJj JfGhdJ YUjQ GdMQfcT cGfJ Ph JCKjQ eNJda, GhbaJ LejY GdJZjjQGJ GdJj Je PcQgG eSHbG hJe OQGSJgG aj bTQg GdOeGZ(B. (3aj GdfgGjg cGf GdGSJfJGL Gf JfGhd (B5 (3ed(B/(3cLe ef YUjQ GdMQfcT dg JCKjQ aj GdhbGjI ddGYUGH VO GdGNJdGd GdYUjHI GdeUGMHg ddScQj aj GdLQPGf(B. (3gPg GdfJGFL JYhO Gdj NUGFU GdMQfcT ceVGOGJ GdCcSOI heVGO ehJ GdNdGjG GdeHQeL heVGO ddGdJgGH(B.s
Thesis (M.Sc.)-Cairo University,2022. Thesis (Ph.D)-Cairo University,2022.
Bibliography: p. 78-92.
Keywords: Biochemistry; Brain